2016
DOI: 10.1002/2015ms000536
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to improve SRTM DEM using multispectral imagery and artificial neural network

Abstract: Although the Shuttle Radar Topography Mission [SRTM) data are a publicly accessible Digital Elevation Model [DEM) provided at no cost, its accuracy especially at forested area is known to be limited with root mean square error (RMSE) of approx. 14 m in Singapore's forested area. Such inaccuracy is attributed to the 5.6 cm wavelength used by SRTM that does not penetrate vegetation well. This paper considers forested areas of central catchment of Singapore as a proof of concept of an approach to improve the SRTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…Kedua data DSM tersebut memiliki perbedaan nilai akurasi vertikal. SRTM merupakan salah satu data DSM terbaik yang terbuka untuk umum namun memiliki ketelitian vertikal yang rendah (Wendi et al, 2016). Tujuan dari penelitian ini adalah melakukan evaluasi perbandingan ketelitian horizontal dari orthorektifikasi citra satelit resolusi sangat tinggi menggunakan dua data DSM yang berbeda yaitu SRTM dan Terrasar-X untuk pemetaan skala besar.…”
Section: Pendahulanunclassified
“…Kedua data DSM tersebut memiliki perbedaan nilai akurasi vertikal. SRTM merupakan salah satu data DSM terbaik yang terbuka untuk umum namun memiliki ketelitian vertikal yang rendah (Wendi et al, 2016). Tujuan dari penelitian ini adalah melakukan evaluasi perbandingan ketelitian horizontal dari orthorektifikasi citra satelit resolusi sangat tinggi menggunakan dua data DSM yang berbeda yaitu SRTM dan Terrasar-X untuk pemetaan skala besar.…”
Section: Pendahulanunclassified
“…Water 2020, 12, x FOR PEER REVIEW 2 of 14 penetrate vegetation well [9]. The absolute vertical SRTM error was found to be 22.35 m across 255,646 samples in the Amazon rainforest [10], whilst in open areas of South America the equivalent error was at 6.2 m [5].…”
Section: Introductionmentioning
confidence: 97%
“…Although it is provided at no cost, its accuracy is limited, with a root mean square error (RMSE) of more than 8 m in Singapore's dense urban/forest areas [8]. It was reported that SRTM suffers from inaccuracy especially in areas covered by the canopy, as the 5.6 cm wavelength used does not penetrate vegetation well [9]. The absolute vertical SRTM error was found to be 22.35 m across 255,646 samples in the Amazon rainforest [10], whilst in open areas of South America the equivalent error was at 6.2 m [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Publish work on swamp forest ecology and the development of ecohydrological models in international, peerreviewed scientific journals So far, one guide book (Ho et al, 2016), one book chapter , nine journal papers (Neo et al, , 2017Sun et al, 2015Sun et al, , 2016Chong et al, 2016;Li et al, 2016;Lim et al, 2016;Tan et al, 2016;Wendi et al, 2016) and 18 conference papers have been published. Another eight papers have been accepted for publication Chong et al, 2018;Clews et al, 2018;Ho et al, 2018;Kutty et al, 2018;Lim et al, 2018;Nguyen et al, 2018;Sun et al, 2018).…”
Section: # Aims Achievementsmentioning
confidence: 99%